2017
DOI: 10.5130/ajceb.v17i3.5520
|View full text |Cite
|
Sign up to set email alerts
|

Challenges, success factors and strategies for women’s career development in the Australian construction industry

Abstract: Construction is traditionally a male industry. Women have long had difficulties entering or advancing their career in construction. Evidence shows that a diversified workforce with gender balance will bring about higher levels of productivity. Despite the importance of this issue, there have been limited studies on women’s career development in construction. This study aims to investigate women’s career development in the Australian construction industry, with objectives to evaluate the challenges and success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 17 publications
2
63
0
1
Order By: Relevance
“…Using the professional background of the respondents, the result revealed that there was a statistically significant difference at the p < 0.05 level in the measures for the four professions: F (3, 45) = 4.109, p-value = 0.012 in the measure of having female mentors/ role models programmes as a way of balancing the female identity in the construction industry. The result of using female mentor/role models to balance the female identity in the construction industry is supported by several studies (Bagilhole, Dainty and Neale, 2002;Amaratunga et al, 2006;Adogbo et al, 2015;Rosa et al, 2017). Role models, mentors or significant others have been identified in research as the most valuable resource in a women's career development and profession (Ericksen and Schultheiss, 2009).…”
Section: Measures To Balance the Female Identity In The Construction mentioning
confidence: 94%
See 2 more Smart Citations
“…Using the professional background of the respondents, the result revealed that there was a statistically significant difference at the p < 0.05 level in the measures for the four professions: F (3, 45) = 4.109, p-value = 0.012 in the measure of having female mentors/ role models programmes as a way of balancing the female identity in the construction industry. The result of using female mentor/role models to balance the female identity in the construction industry is supported by several studies (Bagilhole, Dainty and Neale, 2002;Amaratunga et al, 2006;Adogbo et al, 2015;Rosa et al, 2017). Role models, mentors or significant others have been identified in research as the most valuable resource in a women's career development and profession (Ericksen and Schultheiss, 2009).…”
Section: Measures To Balance the Female Identity In The Construction mentioning
confidence: 94%
“…The study engaged a quantitative angle to obtain answers to the questions posed by the study. Previous studies supporting the choice of the methodology include Adogbo et al (2015) and Rosa et al (2017). A survey research method was utilised with a structured questionnaire instrument in order to elicit information from the respondents of the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation affects their work-life negatively (Oo, Feng, & Lim, 2019;Turner, 2016). It is also observed that the construction industry working style is difficult, with relatively less rest time as the employees sometimes work in standby mode (Rosa, Hon, Xia, & Lamari, 2017). The demand for long working hours contributes to work-life conflicts (Rosa et al, 2017) through adverse outcomes such as stress (Turner & Mariani, 2016).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Persepsi negatif terhadap perempuan juga terjadi dalam industri konstruksi. Suatu penelitian menjelaskan bahwa dalam persepsi negatif terhadap perempuan menjadi hal yang sangat konsen dalam pengembangan karir perempuan di industri konstruksi (Rosa et al, 2017). Tindakan diskriminasi di dunia kerja tidak hanya berdampak pada progres dari pekerja profesional perempuan di bidang konstruksi, tetapi juga akan berpengaruh terhadap kondisi psikis dari mereka (Maskell-Pretz & Hopkins, 2002).…”
Section: B Tinjauan Pustakaunclassified